2023
DOI: 10.1126/sciadv.adj0101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a pharyngeal mucosal lymphoid organ in zebrafish and other teleosts: Tonsils in fish?

Julien Resseguier,
Mai Nguyen-Chi,
Jens Wohlmann
et al.

Abstract: The constant exposure of the fish branchial cavity to aquatic pathogens causes local mucosal immune responses to be extremely important for their survival. Here, we used a marker for T lymphocytes/natural killer (NK) cells (ZAP70) and advanced imaging techniques to investigate the lymphoid architecture of the zebrafish branchial cavity. We identified a sub-pharyngeal lymphoid organ, which we tentatively named “Nemausean lymphoid organ” (NELO). NELO is enriched in T/NK cells, plasma/B cells, and antigen-present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…The same study found a proliferation of B cells in the O-NALT after nasal vaccination, while other areas of the nasal cavity without known organized lymphoid structures did not demonstrate the same type of response [59]. Finally, this year, a pre-print manuscript was made available, describing an organized lymphoid structure named the Nemausen Lymphoid Organ (NEMO), found in the branchial cavity of teleost fish; this may be part of a larger immune complex including the ILT and ALT [60]. The recent increase in the identification of organized lymphoid structures over the last five years demonstrates how little is known about some areas of the teleost immune system.…”
Section: Organized Mucosal Lymphoid Tissuesmentioning
confidence: 99%
“…The same study found a proliferation of B cells in the O-NALT after nasal vaccination, while other areas of the nasal cavity without known organized lymphoid structures did not demonstrate the same type of response [59]. Finally, this year, a pre-print manuscript was made available, describing an organized lymphoid structure named the Nemausen Lymphoid Organ (NEMO), found in the branchial cavity of teleost fish; this may be part of a larger immune complex including the ILT and ALT [60]. The recent increase in the identification of organized lymphoid structures over the last five years demonstrates how little is known about some areas of the teleost immune system.…”
Section: Organized Mucosal Lymphoid Tissuesmentioning
confidence: 99%
“…It is recommended that a new standard for assessing the severity of NF should be evaluated. [19][20][21][22][23][24][25] This study examines the correlation between sequential serum neutrophil levels and the overall improvement status or reduction rate of intravenous antibiotic administration. This study seeks to identify a cost-effective and easily accessible biomarker that can accurately predict the need for hospitalisation in patients with acute tonsillitis who are receiving intravenous broad-spectrum antibiotics.…”
Section: Introductionmentioning
confidence: 99%